Phytochemical Profiling and Biological Assessment of Curcuma aromatica Using UPLC-MS, In silico, and In vitro Approaches for Acne Treatment - Vasanth, Sandhya; Fahma, Amal; Kanekar, Saptami; Raju, Rajesh; Rehman, Niyas; Ahmed, Mohammed Gulzar (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Acne vulgaris is a dermatological condition involving sebaceous gland dysfunction and is characterized by excess sebum secretion, follicular hyperkeratinization, bacterial growth, and inflammation. Curcuma aromatica (C. aromatica), commonly known as wild turmeric, is a medicinal rhizome rich in bioactive phytochemicals. It is a potential source of anti-acne agents due to its antimicrobial, anti-inflammatory, and antioxidant properties. Materials and Methods: Extraction of C. aromatica was carried out using successive solvent extraction, and the phytochemical constituents were analyzed through both qualitative and quantitative methods. Untargeted metabolite profiling of the ethyl acetate extract was performed using HRLC-MS/MS. In addition, an in silico molecular docking study was conducted against the P. acnes hyaluronate lyase enzyme, followed by ADMET evaluation of the identified compounds and assessment of their in vitro antioxidant activity. Results: HRLC-MS/MS profiling identified 191 positive and 67 negative ionizations of secondary metabolites, predominantly flavonoids, phenols, and terpenoids, in the ethyl acetate extract of C. aromatica. The extract exhibited potent antioxidant activity (IC50:168.92 μg/mL), comparable to that of ascorbic acid. Molecular docking studies revealed strong binding affinities of key metabolites sesaminol diglucoside, morusimic acid E, and Floralginsenoside O against hyaluronate lyase enzyme of P. acnes, suggesting potential anti-acne activity. Conclusion: Our findings highlight the therapeutic potential of C. aromatica for the development of novel anti-acne agents with improved safety profiles, and demand future studies focusing on clinical trials.
Keywords: Acne Vulgaris; Antioxidant; Curcuma aromatica; HRLC-MS/MS; In silico; Propionibacterium acnes